A educação infantil (4 e 5 anos de idade) no contexto das escolas de ensino fundamental do município de São Pedro do Sul/RS: estão sendo garantidos os direitos da criança nessa primeira etapa da educação básica? - Müller, Franciele Linke (2022)
This master's thesis was part of the research line LP1: Policies and Management of Basic and Higher Education, of the Graduate Program in Public Policies and Educational Management, at the Federal University of Santa Maria/RS. It addressed the theme “Child Education (4 and 5 years old) in the context of elementary schools in the city of São Pedro do Sul/RS: are children's rights being guaranteed in this first stage of Basic Education?”. Its general objective was to analyze the Political Pedagogical Project and the physical structure of Elementary Schools with Early Childhood Education classes in the Municipality of São Pedro do Sul/RS so that it can be understood whether the rights of children are being guaranteed at this stage of Basic Education. ; because having Kindergarten classes in Elementary Schools is a real trend. As for the specific objectives, priority was given to: investigating the legal frameworks and foundations of Early Childhood Education in Brazil; to map the Municipal Elementary Schools that had Early Childhood Education classes (4 and 5 years old) inserted in their school spaces; to analyze the pedagogical proposals of the schools surveyed from the conceptions and public policies for Early Childhood Education in force in Brazil (macro to micro sphere); to build a draft of a specific guiding document for Early Childhood Education, in order to corroborate with the Municipal Resolution CME No. 02/2019, which establishes basic guidelines for the elaboration or adequacy of the Pedagogical Policy Proposal of Early Childhood Education and Elementary Education establishments of the Municipal System of Teaching in São Pedro do Sul/RS and; to propose the alteration of the nomenclatures of the Municipal Schools of Elementary Education that also have the Infant Education stage so that they are changed to Municipal Schools of Infant Education and Elementary Education. The research had a qualitative approach, of the case study type, having as its object the municipal network of São Pedro do Sul/RS. The techniques used for data construction were documental research and a questionnaire directed to the study subjects who were teachers and managers of the schools surveyed. The theoretical framework was organized based on some authors, such as: Minayo (2009); Yin (2001); Rosenberg (1999); Moss (2011); Kuhlmann (2003); Kramer (2006); Rinaldi (1999); Vieira (2011); Flowers; Brusius; Santos (2018). The idealized product was the construction of a draft guidance document specific to Early Childhood Education to corroborate CME Resolution No. 02/2019, which establishes basic guidelines for the elaboration or adequacy of the Pedagogical Policy Proposal of Early Childhood Education and Elementary Education establishments of the Municipal System of Education in the city of São Pedro do Sul/RS and; It was also proposed to the Education Department and City Council of the municipality to change the nomenclature of the Municipal Schools of Elementary Education that also have the Early Childhood stage so that they are changed to Municipal Schools of Early Childhood Education and Elementary Education in order to enhance and reinforce the importance of childhood spaces in these institutions. It is hoped with this research to broaden the discussion on guaranteeing children's rights at this stage of Basic Education in the context of elementary schools in the Municipality of São Pedro do Sul/RS.